Effect of hot rolling and primary annealing on the microstructure and texture of a β-stabilised γ-TiAl based alloy. (March 2017) - Erdely, Petra; Staron, Peter; Maawad, Emad; Schell, Norbert; Klose, Joachim; Mayer, Svea; Clemens, Helmut
Abstract: Titanium aluminide alloys based on the ordered γ-TiAl phase are intermetallic materials well suited for lightweight high-temperature applications. The TNM alloys, a specific, β-solidifying group among them with a nominal composition of Ti-43.5Al-4Nb-1Mo-0.1B (at.-%), offer a homogeneous and fine-grained microstructure upon casting. This advantage has been exploited to develop a lab-scale hot rolling process in which a cost-effective ingot breakdown of the starting material is omitted. The present work establishes a fundamental understanding of the processes prevailing in the material during hot rolling and primary annealing. Microstructural analysis and texture measurements conducted at a synchrotron radiation source allow to study deformation, recovery, recrystallisation, as well as phase transformation mechanisms in detail. Different hot rolling procedures conducted within the (α+β) and (α+β/βo +γ) regions of the phase diagram are considered and investigated with regard to the prevalent mechanisms. Hot rolling in the (α+β) region entails an α2 phase texture novel in γ-TiAl based alloys. Hot rolling in the (α+β/βo +γ) region near the γ-solvus temperature particularly promotes the breakdown of the initial microstructure in TNM alloys. A specially designed hot rolling process prevents the accumulation of a modified cube texture component in the γ-TiAl phase that is typically linked to anisotropic mechanical properties. Graphical abstract: Image 1